2018
DOI: 10.1080/10408398.2017.1423277
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lipids with potential to affect satiety: Mechanisms and evidence

Abstract: Dietary fat has been implicated in the rise of obesity due to its energy density, palatability and weak effects on satiety. As fat is a major contributor to overall energy intake, incorporating fat with satiating properties could potentially reduce energy intake. This review outlines the potential mechanisms, as far as we know, by which Medium-Chain Triglycerides (MCT), Conjugated Linoleic Acid (CLA), Short-Chain Fatty Acids (SCFA), Diacylglycerol (DAG), n-3 PUFA, and Small Particle Lipids, exerts their satiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 242 publications
(350 reference statements)
0
27
1
Order By: Relevance
“…'Functional fats' are fats which replace other fats with deleterious effects, or which promote beneficial effects to health [6]. Medium-chain triglycerides (MCT) are the most well-researched and currently popular 'functional fat' in terms of satiety, but there are various other fats which also have the potential to beneficially affect weight status and health [7].…”
Section: Introductionmentioning
confidence: 99%
“…'Functional fats' are fats which replace other fats with deleterious effects, or which promote beneficial effects to health [6]. Medium-chain triglycerides (MCT) are the most well-researched and currently popular 'functional fat' in terms of satiety, but there are various other fats which also have the potential to beneficially affect weight status and health [7].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous clinical trials have demonstrated beneficial effects of omega3 supplementation in inflammatory and autoimmune diseases, i.e., lupus erythematosus, rheumatoid arthritis, ulcerative colitis, and also in neuroinflammatory and neurodegenerative diseases [126][127][128][129]. Neurogenic inflammation and genetic factors have an important role in the pathogenesis of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…This may affect gastric mobility and the intestinal passage ratio, possibly changing the rate of NDF fermentation in the gut. This is supported by the slowing gastric emptying rate for the digestion of lipids with longer carbon chains (Hunt and Knox, 1968) and the stimulation of cholecystokinin, a key hormone that reduces intestinal mobility (Maher and Clegg, 2018). Furthermore, oxidized oil is associated with toxic products (e.g., acrolein, 4-hydroxynonenal, and malondialdehyde) resulting from the degradation of lipid peroxides (Shurson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%